High birth order pregnancy and unmet need of contraception in semi-urban population in India: a comparison of two cross sectional surveys performed 10 years apart - Chadha, Shikha; Mittal, Shweta; Sharma, Parwati (International Journal Of Community Medicine And Public Health, 2020)
Background: Rising population is the greatest problem facing the country. The current study was done to find out reasons behind the failure of two child norm policy and to find out the changes in last 10 years in this regard. Methods: A cross sectional survey was done at a referral hospital involving the pregnant women with two or more live children. The Performa used for survey was same as that used 10 years back for a similar study. A comparative analysis was done. Results: A large number of high birth order pregnancies remains unintended (47.47% versus 46.06%). Intended pregnancies still reflect a preference for male child (58.78% versus 54.62%). Unintended pregnancies involves a large population with unmet need of contraception. Conclusions: The prevalence of unmet need for family planning remains high in our society. There is a dire need of better client friendly family planning services especially in antenatal clinics along with educating men and women regarding the importance of planning ones family.